Uncovering allergen presence and accumulation in glucose monitoring systems: evidence of a “sponge effect” via validated GC–MS - Asia Saorin; Sarah Watson; Colin P. Hawkes; John F. Bourke; Niamh M. O’Boyle (Analytica Chimica Acta, 2026)

Long-term predictive modeling of stream condition suggests wide-spread changes within the Chesapeake Bay Watershed, USA - Kelly O. Maloney; Benjamin P. Gressler; Lindsey J. Boyle; Alexander H. Kiser (Hydrobiologia, 2026)
Stream ecosystems worldwide face ongoing degradation, underscoring the urgent need for conservation and restoration. Regional analyses of stream condition have been limited by sparse spatial and temporal data, particularly at long time scales. To address this gap, we used observed data to predict annual biological condition for 360,893 small, nontidal stream reaches in the Chesapeake Bay watershed from 1985 to 2023 (39 years). Predictions were generated using random forest models trained on extensive benthic macroinvertebrate data sets and predictors including natural landscape features, land cover, and climate variables. Four biological metrics were assessed: percent Ephemeroptera, Plecoptera, and Trichoptera excluding Hydropsychidae (EPT-H), percent Ephemeroptera, percent clinger functional group, and the Index of Biological Integrity (IBI). Results revealed degraded biological conditions near Washington, D.C. and Baltimore, Maryland, with declining trends across all metrics in these urbanized areas. Spatial heterogeneity was evident: IBI and clinger percentages increased in many southern streams but declined in northern streams, whereas EPT-H and Ephemeroptera decreased watershed wide except in the Southeastern Plains bioregion. By 2021, watershed wide IBI improvements were predicted for 0.9–1.1% of stream length, falling short of management goals. This study demonstrates the utility of long-term data and machine learning for predicting stream condition, identifying key stressors, and guiding restoration and conservation site selection.

Industrial point source emissions and incident breast and lung cancers: two case–control studies - Joseph Boyle; Patrick Nana-Sinkam; Kandace P. McGuire; Bernard F. Fuemmeler (Cancer Causes & Control, 2026)
Purpose Better understanding of the environment’s role in breast cancer (BC) and lung cancer (LC) incidence is crucial for population health. Growing evidence suggests environmental factors may be relevant for these cancers. We performed two case–control analyses to determine associations between industrial point source emissions, which are proxies for ambient industrial point source-based environmental exposures, and incident BC and LC. Methods We obtained information for 5,801 female adults with BC, 5,250 adults with LC, and 47,956 cancer-free adult controls over 2010–2023. We linked individuals’ residences to releases of 11 agents reported to EPA’s Toxics Release Inventory, determining presence and number of facilities and inverse distance-weighted emissions using several geographic buffer distances and lag times. We fit conditional logistic regression models with multiple comparisons adjustments to datasets derived from three matching methods. Results We identified positive associations between ethylene oxide and chromium exposures with BC. Associations were consistently positive for presence of ethylene oxide-emitting facilities within 5-20 km and chromium-emitting facilities from 5 to 20 km. We identified positive associations between formaldehyde and chromium exposures with LC. Associations were consistently positive for presence of formaldehyde-emitting facilities within 5–20 km and chromium-emitting facilities from 5 to 20 km. Conclusion We observed relationships between industrial point source emissions with BC and LC, particularly for presence of facilities within 5 km of residence. Research should continue examining the role of such emissions for risk of these cancers.

Hazard assessment of insecticidal proteins representing different structural classes using an in vitro experimental platform of human intestinal epithelial monolayers - Cindi S. Zimmermann; Sujatha Rajeev Thundivalappil; Brittany Wilson-Mifsud; Sydney Boyle; Yiwei Wang; Ian Lamb; Matthew Merrell; Carey A. Mathesius; Melissa N. Fallers; JoAnna Bultman; Brenda L. Smith; Anne B. Carlson; et al. (Food and Chemical Toxicology, 2026)

A changing climate might be advantageous for bats hibernating in non-cavernicolous hibernacula - Justin G. Boyles; Jacques P. Veilleux; Lexie A. Schwartz; Dale W. Sparks (Mammal Research, 2026)

Capitalization of urban tree cover: An internal meta-analysis - Shyamani D. Siriwardena; Kevin J. Boyle; Thomas P. Holmes (Ecological Economics, 2025)

Evaluation of soil fungal communities using the ITS2 sublocus and 18S gene primers under different amplification methods - Godar Sene; Chinedu C. Obieze; Obinna T. Ezeokoli; Brian Boyle; Ali M. Quoreshi; Damase P. Khasa (Fungal Ecology, 2025)

Carbon production at shallow‐water artificial reef ecosystems relies on water column primary productivity - Traci Erin Cox; Kelly S. Boyle; Mark A. Albins; Sean P. Powers; Just Cebrian (Limnology and Oceanography, 2025)
The attraction‐production continuum in fishery management centers on the extent to which artificial reefs increase fish production or whether they simply redistribute fish. Reef systems could produce carbon to support growth of higher trophic levels. Therefore, we aimed to understand carbon flows at lower trophic levels on shallow‐water (11 m) artificial reefs within a region which hosts an extensive artificial reef network. We described benthic communities and quantified changes in oxygen content within in situ enclosures to assess reef, sediment, and water‐column community metabolism. We tested spatial and temporal differences in metrics by repeatedly sampling at three sites across two seasons for 2 yrs. Suspension feeders were abundant on reef surfaces and these communities were often heterotrophic. In sediments, lancelets, amphipods, and bivalves were scarcer adjacent to the reef (2 m) and more numerous 20 m away. Infauna communities at adjacent reefs were significantly dissimilar, suggesting biotic (e.g., predation) and, or abiotic (e.g., sand scour) conditions cause large differences in infauna communities near reefs. Sediment and water‐column communities were mostly autotrophic and net productivity did not consistently increase or decrease with distance from the reef. Metabolic metrics were often best explained by temporal intervals and site. The integrated system was autotrophic in 9 out of 11 instances where reef, sediment, and water‐column contributed −0.46 to 0.27, −14.8 to 66.8, and 33.5% to 91.4% respectively to net system productivity. When planning artificial reef deployment projects with heterotrophic reefs, managers should ensure ample water‐column space is provisioned to support them trophically.

Temperature‐Related Effects on Disease Susceptibility and Immune Response in Redband Trout ( Oncorhynchus mykiss gairdneri ) Following Challenge With Flavobacterium columnare - Joshua P. Egan; Jie Ma; Veronica L. Myrsell; Zhongqi Chen; Jonathan Masingale; Christopher C. Caudill; Timothy Boyle; Julianna Browning; Shawn R. Narum; Kenneth D. Cain; Paul A. Hohenlohe (Journal of Fish Diseases, 2025)
Heat stress can increase disease risk in fishes by reducing immune function. Interactions between redband trout ( Oncorhynchus mykiss gairdneri ) and Flavobacterium columnare , a causative agent of columnaris disease, provide an opportunity to investigate the effects of temperature on immune function and disease resistance during periods of thermal stress. We conducted three trials to characterise differences in immune function and mortality between redband trout held at 18°C and 21°C following challenge with F . columnare . In trial 1, cumulative per cent mortality (CPM) was low and not statistically different between 18°C and 21°C. In trials 2 and 2, we administered higher challenge doses and observed increased CPM overall and significantly greater CPM at 21°C than 18°C. Redband trout upregulated il‐8 , tnf‐α , igm and igt following infection by F . columnare , suggesting that all of these genes may be involved in immune responses to F . columnare infection. We found no differences in the strength of the immune responses between fish held at 21°C versus 18°C. This indicated that 21°C did not elicit sufficient thermal stress to impair immune function and that increased CPM at 21°C versus 18°C was due to enhanced F . columnare virulence.

Comparison of traditional copromicroscopy with image analysis devices for detection of gastrointestinal nematode infection in sheep - Amanda McEvoy; Padraig O’Boyle; Saoirse Ellis; John P. Dalton; Michael Parkinson; Orla M. Keane; Cynthia Machín (Veterinary Parasitology, 2024)

A study of fluid overpressure microstructures from the creeping segment of the San Andreas fault - Jafar Hadizadeh; Alan P. Boyle; Andrea E. Gaughan (Journal of Structural Geology, 2024)

Loss of research and operational equipment in Antarctica: Balancing scientific advances with environmental impact - Kevin A. Hughes; Claire P. Boyle; Kate Morley-Hurst; Laura Gerrish; Steve R. Colwell; Peter Convey (Journal of Environmental Management, 2023)

Black pepper pathogen suppression: Divergent rhizosphere fungal communities of healthy and diseased plants yield new insights for orchard management in Vietnam - Chinedu C. Obieze; Paul B.L. George; Brian Boyle; Damase P. Khasa (Fungal Ecology, 2023)

Living mulches reduce natural enemies when combined with frequent pesticide applications - T. Blake Hudson; Adam M. Alford; Tom R. Bilbo; Sean C. Boyle; Helene B. Doughty; Thomas P. Kuhar; Lorena Lopez; Kelly C. McIntyre; Allison K. Stawara; James F. Walgenbach; Courtney Walls; Carmen K. Blubaugh (Agriculture, Ecosystems & Environment, 2023)

Development of a novel real-time PCR multiplex assay for detection of Streptococcus equi subspecies equi and Streptococcus equi subspecies zooepidemicus - Ellen Ruth A. Morris; Megan E. Schroeder; Pamela J. Ferro; Andrew S. Waller; Abigail A. McGlennon; Carla P. Bustos; Leticia T. Gressler; Jing Wu; Sara D. Lawhon; Ashley G. Boyle; Sonia Lingsweiler; Narayan Paul; et al. (Veterinary Microbiology, 2023)

Inactivation of HCoV-NL63 and SARS-CoV-2 in aqueous solution by 254 nm UV-C - Lily X. Li; Ruth H. Nissly; Anand Swaminathan; Ian M. Bird; Nina R. Boyle; Meera Surendran Nair; Denver I. Greenawalt; Abhinay Gontu; Victoria S. Cavener; Ty Sornberger; James D. Freihaut; Suresh V. Kuchipudi; et al. (Journal of Photochemistry and Photobiology B: Biology, 2023)

Black pepper rhizomicrobiome: Spectrum of plant health indicators, critical environmental factors and community compartmentation in Vietnam - Chinedu C. Obieze; Paul B.L. George; Brian Boyle; Damase P. Khasa (Applied Soil Ecology, 2023)

Bibliometric investigation of the integration of animal personality in conservation contexts - Sydney M. Collins; Jack G. Hendrix; Quinn M. R. Webber; Sean P. Boyle; Katrien A. Kingdon; Robert J. Blackmore; Kyle J. N. d'Entremont; Jennifer Hogg; Juan P. Ibáñez; Joanie L. Kennah; Jessika Lamarre; Miguel Mejías; et al. (Conservation Biology, 2023)
Consistent individual differences in behavior, commonly termed animal personality , are a widespread phenomenon across taxa that have important consequences for fitness, natural selection, and trophic interactions. Animal personality research may prove useful in several conservation contexts, but which contexts remains to be determined. We conducted a structured literature review of 654 studies identified by combining search terms for animal personality and various conservation subfields. We scored the relevance of personality and conservation issues for each study to identify which studies meaningfully integrated the 2 fields as opposed to surface‐level connections or vague allusions. We found a taxonomic bias toward mammals (29% of all studies). Very few amphibian or reptile studies applied personality research to conservation issues (6% each). Climate change (21%), invasive species (15%), and captive breeding and reintroduction (13%) were the most abundant conservation subfields that occurred in our search, though a substantial proportion of these papers weakly integrated conservation and animal personality (climate change 54%, invasive species 51%, captive breeding and reintroduction 40%). Based on our results, we recommend that researchers strive for consistent and broadly applicable terminology when describing consistent behavioral differences to minimize confusion and improve the searchability of research. We identify several gaps in the literature that appear to be promising and fruitful avenues for future research, such as disease transmission as a function of sociability or exploration as a driver of space use in protected areas. Practitioners can begin informing future conservation efforts with knowledge gained from animal personality research.

Diel patterns of depth use and swimming activity of post-release greater amberjack (Seriola dumerili) in the northern Gulf of Mexico - Kelly S. Boyle; Crystal L. Hightower; Sean P. Powers (Environmental Biology of Fishes, 2023)

Spotted cucumber beetle (Diabrotica undecimpunctata howardi) is attracted to vittatalactone, the pheromone of striped cucumber beetle (Acalymma vittatum) - Ariela I. Haber; Kayla Pasteur; Filadelfo Guzman; Sean M. Boyle; Thomas P. Kuhar; Donald C. Weber (Journal of Pest Science, 2023)
Spotted cucumber beetle ( Diabrotica undecimpunctata howardi ; also known as southern corn rootworm) is a pest feeding on many crops, including cucurbits, corn (maize), peanuts, beans, and other crops and wild plants in North America. On cucurbit crops, where it co-occurs with striped cucumber beetle ( Acalymma vittatum ), both are key pests that vector Erwinia tracheiphila, a destructive pathogen that causes bacterial wilt. Here we deployed synthetic vittatalactone, the male-produced aggregation pheromone of A. vittatum , as lures in the field, to measure attraction of the target and non-target insects. Both sexes of D. u. howardi were strongly attracted to the vittatalactone lures (5–7.5-fold compared to blank trap) throughout the growing season in Maryland and Virginia, USA. Moreover, D. u. howardi was more attracted to live A. vittatum males feeding on squash plants than to plants with females or without any beetles, confirming the genuine organismal cross-attraction between these two key pests. The kairomonal attraction to vittatalactone suggests that it functions as a “keystone semiochemical,” mediating the colonization of cucurbits by multiple herbivore species. Such cross attraction could allow for use of vittatalactone in management of multiple pest species, with potential reduction of pesticide use in cucurbit crops.

Paracrine Factors Released by Stem Cells of Mesenchymal Origin and their Effects in Cardiovascular Disease: A Systematic Review of Pre-clinical Studies - Nishani S. Mabotuwana; Lavinia Rech; Joyce Lim; Sean A. Hardy; Lucy A. Murtha; Peter P. Rainer; Andrew J. Boyle (Stem Cell Reviews and Reports, 2022)
Mesenchymal stem cell (MSC) therapy has gained significant traction in the context of cardiovascular repair, and have been proposed to exert their regenerative effects via the secretion of paracrine factors. In this systematic review, we examined the literature and consolidated available evidence for the “paracrine hypothesis”. Two Ovid SP databases were searched using a strategy encompassing paracrine mediated MSC therapy in the context of ischemic heart disease. This yielded 86 articles which met the selection criteria for inclusion in this study. We found that the MSCs utilized in these articles were primarily derived from bone marrow, cardiac tissue, and adipose tissue. We identified 234 individual protective factors across these studies, including VEGF, HGF, and FGF2; which are proposed to exert their effects in a paracrine manner. The data collated in this systematic review identifies secreted paracrine factors that could decrease apoptosis, and increase angiogenesis, cell proliferation, and cell viability. These included studies have also demonstrated that the administration of MSCs and indirectly, their secreted factors can reduce infarct size, and improve left ventricular ejection fraction, contractility, compliance, and vessel density. Furthering our understanding of the way these factors mediate repair could lead to the identification of therapeutic targets for cardiac regeneration. Graphical abstract

Diel, temporal, and spatial patterns of biotic soundscapes among Alabama artificial reefs in late spring and summer - Kelly S. Boyle; Crystal L. Hightower; T. Reid Nelson; Sean P. Powers (Frontiers in Marine Science, 2022)
Passive acoustic monitoring (PAM) in a variety of marine habitats has revealed distinct spatial and temporal variation of fish sounds that are predicted to vary in association with species composition and abundance, as well as diel and seasonal influences. Reefs in the Alabama Artificial Reef Zone (AARZ) in the northern Gulf of Mexico (nGOM) have an associated fish fauna composed of warm-temperate and tropical reef associated species. AARZ reefs are made of different structures (e.g. bridge rubble, concrete pyramids, etc.) and as a result, their fish species composition is predicted to vary. We used PAM to describe fish sounds on 18 shallow slope (20-33 m) AARZ reefs in 2017 and 2018. We detected calls from unknown sources, as well as sounds from leopard toadfish Opsanus pardus , cocoa damselfish Stegastes variabilis , and cusk-eels (Ophidiidae). We developed semi-automated screening methods to detect specific sound types and described diel and spatial patterns. Sound detection rates varied widely among reefs, but not by reef type. Number of sound types increased with species richness, but detection rates of specific sounds differed on reefs with similar species composition. Our results indicate that many frequently occurring sounds may not be associated with visually conspicuous fishes. Further research is needed to determine source species and associated behavior for common sounds in these habitats. Soundscape variability among nGOM artificial reefs may be a consideration for management, as biological sound can provide an acoustic cue for reef location by some larval and adult fish species.

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

Carbohydrate mouth rinsing does not affect 6-min walk test performance and blood glucose responses in older adults - Elizabeth S. Evans; Terrence Brophy; Matthew R. Braswell; Joshua Boyle; G. Keith Harris; Ruth H. Watkins; Stephen P. Bailey (European Journal of Applied Physiology, 2021)

Brain-predicted age difference score is related to specific cognitive functions: a multi-site replication analysis - Rory Boyle; Lee Jollans; Laura M. Rueda-Delgado; Rossella Rizzo; Görsev G. Yener; Jason P. McMorrow; Silvin P. Knight; Daniel Carey; Ian H. Robertson; Derya D. Emek-Savaş; Yaakov Stern; Rose Anne Kenny; et al. (Brain Imaging and Behavior, 2021)

Limited evidence for negative effects of highway widening on North American large mammals - Sean P. Boyle; Jacqueline D. Litzgus; David Lesbarrères (European Journal of Wildlife Research, 2020)

The Toxicology Investigators Consortium Case Registry—the 2019 Annual Report - Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Kim Aldy; Diane P. Calello; Sharan L. Campleman; Shao Li; Gillian A Beauchamp; Timothy Wiegand; Paul M. Wax; Jeffery Brent; P. A. Akpunonu; et al. (Journal of Medical Toxicology, 2020)

Site use and connectivity of female grey seals (Halichoerus grypus) around Wales - Izzy Langley; Tobias Rosas da Costa Oliver; Lex Hiby; Thomas B. Stringell; Ceri W. Morris; Oliver O’Cadhla; Lisa Morgan; Kate Lock; Sarah Perry; Stephen Westcott; Dave Boyle; Birgitta I. Büche; et al. (Marine Biology, 2020)
Grey seals ( Halichoerus grypus ) are a qualifying feature of three special areas of conservation (SACs) in Wales, yet relatively little is known of their site use along this coastline. Since 1992, many individuals and organisations have contributed to a grey seal photographic identification database held by Natural Resources Wales, which is one of the largest and oldest of its kind, providing key information from grey seal haul-out sites around the Celtic and Irish Seas. Here, we investigated spatial connectivity of haul-out sites and fidelity of adult females to breeding sites. The minimum number of adult female grey seals using the area between 1992 and 2016 was 2688. Individual capture histories and relative spatial transition probabilities ( P ij ) between pairs of location groups were calculated. Adjacent locations were highly connected (e.g. Lleyn Peninsula and Bardsey, P ij = 0.7) but connections spanned the entire region, up to 230 km apart (e.g. Skomer and Dee Estuary, P ij = 0.004). Resights were recorded within SACs (e.g. Lleyn Peninsula and Bardsey [Lleyn Peninsula and the Sarnau SAC], P ij = 0.7), between SACs (e.g. Bardsey and Skomer [Pembrokeshire Marine], P ij = 0.03), between SACs and non-designated areas (e.g. Skerries and Bardsey, P ij = 0.09) and between sites outside any protected area (e.g. Dee Estuary and Anglesey, P ij = 0.5). While inter-annual fidelity to breeding sites was high ( P ij = 0.82–1), individual female grey seals moved throughout the region. This evidence of extensive site use beyond protected areas is important for the management and conservation of grey seals around Wales.

Harmony on the prairie? Grassland plant and animal community responses to variation in climate across land‐use gradients - Lindsey A. Bruckerhoff; R. Kent Connell; James P. Guinnip; Elina Adhikari; Alixandra Godar; Keith B. Gido; Alice W. Boyle; Andrew G. Hope; Anthony Joern; Ellen Welti (Ecology, 2020)
Human induced climate and land‐use change are severely impacting global biodiversity, but how community composition and richness of multiple taxonomic groups change in response to local drivers and whether these responses are synchronous remains unclear. We used long‐term community‐level data from an experimentally manipulated grassland to assess the relative influence of climate and land use as drivers of community structure of four taxonomic groups: birds, mammals, grasshoppers, and plants. We also quantified the synchrony of responses among taxonomic groups across land‐use gradients and compared climatic drivers of community structure across groups. All four taxonomic groups responded strongly to land use (fire frequency and grazing), while responses to climate variability were more pronounced in grasshoppers and small mammals. Animal groups exhibited asynchronous responses across all land‐use treatments, but plant and animal groups, especially birds, exhibited synchronous responses in composition. Asynchrony was attributed to taxonomic groups responding to different components of climate variability, including both current climate conditions and lagged effects from the previous year. Data‐driven land management strategies are crucial for sustaining native biodiversity in grassland systems, but asynchronous responses of taxonomic groups to climate variability across land‐use gradients highlight a need to incorporate response heterogeneity into management planning.

Nocturnal reductions in body temperature in high-elevation Neotropical birds - Keith Burnett; Matthew N. Zipple; Lauren T. Phillips; Pooja Panwar; Liam P. Mcguire; W. Alice Boyle (Tropical Ecology, 2019)

Essential in vitro diagnostics for advanced HIV and serious fungal diseases: international experts’ consensus recommendations - Felix Bongomin; Nelesh P. Govender; Arunaloke Chakrabarti; Florence Robert-Gangneux; David R. Boulware; Afia Zafar; Rita O. Oladele; Malcolm D. Richardson; Jean-Pierre Gangneux; Ana Alastruey-Izquierdo; Joel Bazira; Tom H. Boyles; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Termite environmental tolerances are more linked to desiccation than temperature in modified tropical forests - J. S. Woon; M. J. W. Boyle; R. M. Ewers; A. Chung; P. Eggleton (Insectes Sociaux, 2019)

Testing traditional assumptions about regional migration in bats - Jennifer J. Krauel; Liam P. McGuire; Justin G. Boyles (Mammal Research, 2018)

Comparison of road surveys and circuit theory to predict hotspot locations for implementing road-effect mitigation - S. P. Boyle; J. D. Litzgus; David Lesbarrères (Biodiversity and Conservation, 2017)

5-HT modulation of pain perception in humans - Sarah L. Martin; Andrea Power; Yvonne Boyle; Ian M. Anderson; Monty A. Silverdale; Anthony K. P. Jones (Psychopharmacology, 2017)

Pan-European inter-laboratory studies on a panel of in vitro cytotoxicity and pro-inflammation assays for nanoparticles - Jean-Pascal Piret; Olesja M. Bondarenko; Matthew S. P. Boyles; Martin Himly; Ana R. Ribeiro; Federico Benetti; Caroline Smal; Braulio Lima; Annegret Potthoff; Monica Simion; Elise Dumortier; Paulo Emilio C. Leite; et al. (Archives of Toxicology, 2017)

Run, hide, or fight: anti-predation strategies in endangered red-nosed cuxiú (Chiropotes albinasus, Pitheciidae) in southeastern Amazonia - Adrian A. Barnett; João M. Silla; Tadeu de Oliveira; Sarah A. Boyle; Bruna M. Bezerra; Wilson R. Spironello; Eleonore Z. F. Setz; Rafaela F. Soares da Silva; Samara de Albuquerque Teixeira; Lucy M. Todd; Liliam P. Pinto (Primates, 2017)

High-density marker profiling confirms ancestral genomes of Avena species and identifies D-genome chromosomes of hexaploid oat - Honghai Yan; Wubishet A. Bekele; Charlene P. Wight; Yuanying Peng; Tim Langdon; Robert G. Latta; Yong-Bi Fu; Axel Diederichsen; Catherine J. Howarth; Eric N. Jellen; Brian Boyle; Yuming Wei; et al. (Theoretical and Applied Genetics, 2016)

A plant growth form dataset for the New World - K. Engemann; B. Sandel; B. Boyle; B. J. Enquist; P. M. Jørgensen; J. Kattge; B. J. McGill; N. Morueta‐Holme; R. K. Peet; N. J. Spencer; C. Violle; S. K. Wiser; et al. (Ecology, 2016)
This dataset provides growth form classifications for 67,413 vascular plant species from North, Central, and South America. The data used to determine growth form were compiled from five major integrated sources and two original publications: the Botanical Information and Ecology Network ( BIEN ), the Plant Trait Database ( TRY ), the SALVIAS database, the USDA PLANTS database, Missouri Botanical Garden's Tropicos database, Wright (2010), and Boyle (1996). We defined nine plant growth forms based on woodiness (woody or non‐woody), shoot structure (self‐supporting or not self‐supporting), and root traits (rooted in soil, not rooted in soil, parasitic or aquatic): Epiphyte, Liana, Vine, Herb, Shrub, Tree, Parasite, or Aquatic. Species with multiple growth form classifications were assigned the growth form classification agreed upon by the majority (>2/3) of sources. Species with ambiguous or otherwise not interpretable growth form assignments were excluded from the final dataset but are made available with the original data. Comparisons with independent estimates of species richness for the Western hemisphere suggest that our final dataset includes the majority of New World vascular plant species. Coverage is likely more complete for temperate than for tropical species. In addition, aquatic species are likely under‐represented. Nonetheless, this dataset represents the largest compilation of plant growth forms published to date, and should contribute to new insights across a broad range of research in systematics, ecology, biogeography, conservation, and global change science.

Late Pleistocene climate inferences from a water balance model of Jakes Valley, Nevada (USA) - Cornelia Barth; Douglas P. Boyle; Benjamin J. Hatchett; Scott D. Bassett; Christopher B. Garner; Kenneth D. Adams (Journal of Paleolimnology, 2016)

A non-canonical role for desmoglein-2 in endothelial cells: implications for neoangiogenesis - Lisa M. Ebert; Lih Y. Tan; M. Zahied Johan; Kay Khine Myo Min; Michaelia P. Cockshell; Kate A. Parham; Kelly L. Betterman; Paceman Szeto; Samantha Boyle; Lokugan Silva; Angela Peng; YouFang Zhang; et al. (Angiogenesis, 2016)

Heme oxygenase-1 regulates cell proliferation via carbon monoxide-mediated inhibition of T-type Ca2+ channels - Hayley Duckles; Hannah E. Boycott; Moza M. Al-Owais; Jacobo Elies; Emily Johnson; Mark L. Dallas; Karen E. Porter; Francesca Giuntini; John P. Boyle; Jason L. Scragg; Chris Peers (Pflügers Archiv - European Journal of Physiology, 2015)

Continuum Approaches to Understanding Ion and Peptide Interactions with the Membrane - Naomi R. Latorraca; Keith M. Callenberg; Jon P. Boyle; Michael Grabe (The Journal of Membrane Biology, 2014)

Development of a rotorcraft dust-emission parameterization using a CFD model - Jerrold D. McAlpine; Darko R. Koracin; Douglas P. Boyle; John A. Gillies; Eric V. McDonald (Environmental Fluid Mechanics, 2010)

High levels of acrylate in the Great Barrier Reef coral Acropora millepora - D. M. Tapiolas; C. A. Motti; P. Holloway; S. G. Boyle (Coral Reefs, 2010)

Textural variation in the pyrite-rich ore deposits of the Røros district, Trondheim Region, Norway: implications for pyrite deformation mechanisms - Craig D. Barrie; Nigel J. Cook; Alan P. Boyle (Mineralium Deposita, 2010)

How many Eurasian badgers Meles meles L. are there in the Republic of Ireland? - D. P. Sleeman; J. Davenport; S. J. More; T. A. Clegg; J. D. Collins; S. W. Martin; D. H. Williams; J. M. Griffin; I. O’Boyle (European Journal of Wildlife Research, 2009)

The effectiveness of barriers to badger Meles meles immigration in the Irish Four Area project - D. P. Sleeman; J. Davenport; S. J. More; T. A. Clegg; J. M. Griffin; I. O’Boyle (European Journal of Wildlife Research, 2009)

Hypoxic Modulation of Ca2+ Signaling in Human Venous and Arterial Endothelial Cells - P. K. Aley; C. C. Bauer; M. L. Dallas; J. P. Boyle; K. E. Porter; C. Peers (The Journal of Membrane Biology, 2009)

Dendrites determine the contribution of after depolarization potentials (ADPs) to generation of repetitive action potentials in hypothalamic gonadotropin releasing-hormone (GnRH) neurons - C. B. Roberts; M. P. O’Boyle; K. J. Suter (Journal of Computational Neuroscience, 2009)

Hypoxic remodelling of Ca2+ signalling in proliferating human arterial smooth muscle - Parvinder K. Aley; Jenny A. Wilkinson; Claudia C. Bauer; John P. Boyle; Karen E. Porter; Chris Peers (Molecular and Cellular Biochemistry, 2008)

H2O2-stimulated Ca2+ influx via TRPM2 is not the sole determinant of subsequent cell death - Jenny A. Wilkinson; Jason L. Scragg; John P. Boyle; Bernd Nilius; Chris Peers (Pflügers Archiv - European Journal of Physiology, 2008)

Outcome and immune responses after Brucella abortus infection in young adult and aged mice - Kevin P. High; Rajeev Prasad; Chad R. Marion; Gerhardt G. Schurig; Stephen M. Boyle; Nammalwar Sriranganathan (Biogerontology, 2007)

The influence of human activity in the Arctic on climate and climate impacts - Henry P. Huntington; Michelle Boyle; Gwenn E. Flowers; John W. Weatherly; Lawrence C. Hamilton; Larry Hinzman; Craig Gerlach; Rommel Zulueta; Craig Nicolson; Jonathan Overpeck (Climatic Change, 2007)

Structure and function of the stomachless digestive system in three related species of New World silverside fishes (Atherinopsidae) representing herbivory, omnivory, and carnivory - M. H. Horn; A. K. Gawlicka; D. P. German; E. A. Logothetis; J. W. Cavanagh; K. S. Boyle (Marine Biology, 2006)

Landsat TM inventory and assessment of waterbird habitat in the southern altiplano of South America - Terence P. Boyle; Sandra M. Caziani; Robert G. Waltermire (Wetlands Ecology and Management, 2004)

Ultrastructural observations of efferent terminals in the crista Ampullaris of the toadfish, opsanus tau - G. R. Holstein; G. P. Martinelli; R. Boyle; R. D. Rabbitt; S. M. Highstein (Experimental Brain Research, 2004)

Ultrastructural observations of efferent terminals in the crista Ampullaris of the toadfish, opsanus tau - G. R. Holstein; G. P. Martinelli; R. Boyle; R. D. Rabbitt; S. M. Highstein (Experimental Brain Research, 2004)

The use of electron backscatter diffraction and orientation contrast imaging as tools for sulphide textural studies: example from the Greens Creek deposit (Alaska) - Alan P. Boyle; Eric Nelson; Murray Hitzman; James Churchill; Magda Lopez-Pedrosa; Katja Freitag (Mineralium Deposita, 2004)

Pharmacological and autoradiographical characterization of serotonin transporter-like activity in sporocysts of the human blood fluke, Schistosoma mansoni - J. P. Boyle; J. F. Hillyer; T. P. Yoshino (Journal of Comparative Physiology A, 2003)

Tactile inhibition of return: non-ocular response inhibition and mode of response - E. Poliakoff; C. Spence; D. J. O’Boyle; F. P. McGlone; F. W. J. Cody (Experimental Brain Research, 2002)

Predation by seals on salmonids in two Scottish estuaries - T. J. Carter; G. J. Pierce; J. R. G. Hislop; J. A. Houseman; P. R. Boyle (Fisheries Management and Ecology, 2001)
Detailed observations of the behaviour of harbour seals, Phoca vitulina L., at sites within the estuaries of the Rivers Dee and Don, in north‐eastern Scotland, were made over two full years between 1993 and 1996. Small numbers of grey seals, Halichoerus grypus Fab., were also present. The presence of seals within the estuaries was strongly related to season, with maximum numbers observed in winter and early spring; seals were virtually absent in June and July. The River Don was used largely as a haul‐out site, while the River Dee was used predominantly as a foraging site, although it was not possible to determine whether the same seals were using the two estuaries. More seals were hauled‐out on the River Don during twilight and dark than in daylight. The seals were observed to eat mostly salmonids, Salmo salar L. and S. trutta L., unidentified roundfish and flounder, Pleuronectes flesus L. The otoliths identified in scats collected at the mouth of the River Don belonged to marine species indicating that the seals were also feeding outside the estuaries. A minimum estimate is given of the numbers of large salmonids eaten in each river during the course of the year. Although no information was available on the numbers of salmonids using the rivers or the reproductive status of the fish eaten by the seals, as a cause of mortality, seal predation on large salmonids in estuaries is apparently an order of magnitude less important than mortality caused by angling within the river.

Assignment of paternity groups without access to parental genotypes: multiple mating and developmental plasticity in squid - A. M. Emery; I. J. Wilson; S. Craig; P. R. Boyle; L. R. Noble (Molecular Ecology, 2001)
We present a novel approach to investigating sibling relationships and reconstructing parental genotypes from a progeny array. The Bayesian method we have employed is flexible and may be applicable to a variety of situations in addition to the one presented here. While mutation rates and breeding population allele frequencies can be taken into account, the model requires relatively few loci and makes few assumptions. Paternity of 270 veined squid ( Loligo forbesi ) hatchlings from three egg strings collected from one location was assigned using five microsatellite loci. Paternal and maternal genotypes reconstructed for each of the three strings were identical, strongly indicating that a single female produced the strings that were fertilized by the same four males. The proportion of eggs fertilized was not equal between males in all three strings, with male 1 siring most offspring (up to 68% in string 1), through to male 4 siring the least (as low as 2.4% in string 1). Although temperature had a profound effect on incubation time, paternity did not affect this trait at 12 °C or 8 °C.

Fecundity and spawning in a deep-water cirromorph octopus - P. R. Boyle; H. I. Daly (Marine Biology, 2000)

Microsatellite markers for investigating population structure in Octopus vulgaris (Mollusca: Cephalopoda) - E. C. Greatorex; C. S. Jones; J. Murphy; L. N. Key; A. M. Emery; P. R. Boyle (Molecular Ecology, 2000)

New microsatellite markers for assessment of paternity in the squid Loligo forbesi (Mollusca: Cephalopoda) - A. M. Emery; P. W. Shaw; E. C. Greatorex; P. R. Boyle; L. R. Noble (Molecular Ecology, 2000)

Environmental Impacts in the Jianghan Plain: Evidence from Lake Sediments - J. F. Boyle; N. L. Rose; H. Bennion; H. Yang; P. G. Appleby (Water, Air, & Soil Pollution, 1999)

Subtle population structuring within a highly vagile marine invertebrate, the veined squid Loligo forbesi , demonstrated with microsatellite DNA markers - P. W. SHAW; G. J. PIERCE; P. R. BOYLE (Molecular Ecology, 1999)
Microsatellite DNA markers were applied for the first time in a population genetic study of a cephalopod and compared with previous estimates of genetic differentiation obtained using allozyme and mitochondrial DNA (mtDNA) markers. Levels of genetic variation detected with microsatellites were much higher than found with previous markers (mean number of alleles per locus=10.6, mean expected heterozygosity ( H E )=0.79; allozyme H E =0.08; mtDNA restriction fragment length polymorphism (RFLP) H E =0.16). In agreement with previous studies, microsatellites demonstrated genetic uniformity across the population occupying the European shelf seas of the North East Atlantic, and extreme genetic differentiation of the Azores population ( R ST / F ST =0.252/0.245; allozyme F ST =0.536; mtDNA F ST =0.789). In contrast to other markers, microsatellites detected more subtle, and significant, levels of differentiation between the populations of the North East Atlantic offshore banks (Rockall and Faroes) and the shelf population ( R ST =0.048 and 0.057). Breakdown of extensive gene flow among these populations is indicated, with hydrographic (water depth) and hydrodynamic (isolating current regimes) factors suggested as possible barriers to migration. The demonstration of genetic subdivision in an abundant, highly mobile marine invertebrate has implications for the interpretation of dispersal and population dynamics, and consequent management, of such a commercially exploited species. Relative levels of differentiation indicated by the three different marker systems, and the use of measures of differentiation (assuming different mutation models), are discussed.

Plastic deformation of metamorphic pyrite: new evidence from electron-backscatter diffraction and forescatter orientation-contrast imaging - A. P. Boyle; D. J. Prior; M. H. Banham; N. E. Timms (Mineralium Deposita, 1998)

Influence of earthworms on soil properties and grass production in reclaimed cutover peat - K. E. Boyle; J. P. Curry; E. P. Farrell (Biology and Fertility of Soils, 1997)

Bacterial PCB biodegradation - Alfred W. Boyle; Christopher J. Silvin; John P. Hassett; James P. Nakas; S. W. Tanenbaum (Biodegradation, 1992)

Role of exposure mode in the bioavailability of triphenyl phosphate to aquatic organisms - James N. Huckins; James F. Fairchild; Terence P. Boyle (Archives of Environmental Contamination and Toxicology, 1991)

Vaccinia virus expression and sequence of an avian influenza nucleoprotein gene: potential use in diagnosis - V. R. Harley; P. J. Hudson; B. E. H. Coupar; P. W. Selleck; H. Westbury; D. B. Boyle (Archives of Virology, 1990)

Uptake of lead from aquatic sediment by submersed macrophytes and crayfish - Matthew F. Knowlton; Terence P. Boyle; John R. Jones (Archives of Environmental Contamination and Toxicology, 1983)